IMPROVING MENTAL HEALTH OUTCOMES IN EPILEPSY: THE EFFECT OF COUNSELLING ON DRUG-INDUCED COGNITIVE AND BEHAVIORAL CHANGES - VINEETHA S; HEMALATHA SELVARAJ; DAVIS MANUEL A (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The objective of the study was to assess the impact of patient counseling on cognitive impairment and behavioral adverse effects associated with antiepileptic drug (AED) therapy among emerging adults with epilepsy. Methods: This prospective pre-post interventional study was conducted in the Department of Neurology at a tertiary care hospital in Kerala from May 2024 to October 2024. A total of 47 patients with epilepsy aged 18–29 years who were receiving AED therapy were included. The impact of patient counseling on cognitive impairment and behavioral adverse effects of AEDs was assessed using baseline and follow-up evaluations. Results: Among the emerging adults with epilepsy, the mean age was approximately 20 years, and males constituted 68% of the study population. Levetiracetam was the most frequently prescribed AED, accounting for 47% of prescriptions. The mean cognitive impairment score decreased from 18.21±0.954 at baseline to 15.32±0.471 at the final follow-up. Similarly, the mean behavioral adverse-effect score decreased from 18.15±1.000 at baseline to 15.21±0.657 at follow-up. These findings indicate improvement in cognitive and behavioral outcomes following patient counseling. Conclusion: Patient counseling appears to improve cognitive and behavioral outcomes in emerging adults receiving AED therapy. Strengthening communication between healthcare providers and patients may enhance treatment understanding, reduce adverse effects, and improve quality of life. Further studies with larger samples and comparative designs are needed to confirm these findings.